2021
DOI: 10.1016/j.jde.2021.01.019
|View full text |Cite
|
Sign up to set email alerts
|

On the existence and the uniqueness of the solution to a fluid-structure interaction problem

Abstract: In this paper we consider the linearized version of a system of partial differential equations arising from a fluid-structure interaction model. We prove the existence and the uniqueness of the solution under natural regularity assumptions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Moreover, after linearization one obtains a two-phase Stokes type problem, which ensures us to get the solvabilities and regularities of fluid and solid velocities by maximal regularity theory. In a recent work [9], a similar stress tensor of solid part was also considered to investigate weak solutions of the interaction between an incompressible fluid and an incompressible immersed viscous-hyperelastic solid structure.…”
mentioning
confidence: 99%
“…Moreover, after linearization one obtains a two-phase Stokes type problem, which ensures us to get the solvabilities and regularities of fluid and solid velocities by maximal regularity theory. In a recent work [9], a similar stress tensor of solid part was also considered to investigate weak solutions of the interaction between an incompressible fluid and an incompressible immersed viscous-hyperelastic solid structure.…”
mentioning
confidence: 99%
“…In [9], it was shown that a linearized version of Problem 1 admits a unique solution. See also [8] for a review on the state of the art about this problem.…”
Section: Fictitious Domain Approach: Problem Settingmentioning
confidence: 99%
“…Starting from here, we then introduced a Lagrange multiplier with the effect that the movement of the structure is managed through a bilinear form that contains the multiplier. As part of our research, several theoretical aspects have been addressed over the years: in [7], we showed the well-posedness of both continuous and discrete problems, in [9] the existence and the uniqueness of the solution were proved in the case of the linearized problem. These results are summarized in a unified setting in [8].…”
Section: Introductionmentioning
confidence: 99%
“…In [6] continuous piecewise bilinear finite element spaces are considered on quadrilateral meshes. Recently, [5] showed, in the framework of FSI, the stability of a linearization of the continuous problem and introduced a unified setting for the choice of the finite element spaces. This setting allows for more general choices of spaces.…”
Section: Introductionmentioning
confidence: 99%